Genetic differences in Lobesia botrana populations : related to host plant or geographic origin? - Döös, Sophia (SLU/Dept. of Plant Breeding (from 130101), 2013)
For the past six decades the model of geographical isolation has been dominating but recently there has been a renewed interest in the possibility of sympatric speciation. Races of phytophagous insects specializing on different species of host plants have often been studied for the purpose of solving the question of sympatric speciation. I have characterized genetic differentiation of populations of a polyphagous moth, Lobesia botrana to compare geographic separation and separation based on different host plants as potential causes for population genetic structure. I have used two molecular marker techniques: microsatellites and AFLPs, and the data was analysed using several statistical methods, with the original aim to compare which of these analyses could be most helpful in providing useful information about genetic differentiation. Both microsatellites and AFLPs detected a genetic variance related to Geographic distance and AFLPs were able to detect significant differentiations related to host plant that the microsatellites were not able to detect. Pair wise genetic distance comparisons indicated a higher differentiation according to host plants than the differentiation according to geographic distance. On the other hand, the overall differentiation between samples from different locations was higher than the differentiation between samples from different host plants. This indicates that a host related adaptation can be going on in L. botrana populations causing reproductive barriers between groups developing on Daphne and groups developing on grapes, but they do not seem to have formed host races yet. Low heterozygosity values and high inbreeding coefficients in the studied populations need further studies to make strong conclusion.